2022
DOI: 10.1038/s41598-022-24816-z
|View full text |Cite
|
Sign up to set email alerts
|

Multi-proxy dentition analyses reveal niche partitioning between sympatric herbivorous dinosaurs

Abstract: Dentitions of the sympatric herbivorous dinosaurs Hungarosaurus (Ankylosauria, Nodosauridae) and Mochlodon (Ornithopoda, Rhabdodontidae) (Santonian, Hungary) were analysed to investigate their dietary ecology, using several complementary methods—orientation patch count, tooth replacement rate, macrowear, tooth wear rate, traditional microwear, and dental microwear texture analysis (DMTA). Tooth formation time is similar in Hungarosaurus and Mochlodon, and traditional and DMTA microwear features suggest low-bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…In the mesiodistal thin-section of rPM5 in the early juvenile CUGW VH132, the tooth formation time is 25 days in the premaxilla (Table 3). This duration is lower than Hungarosaurus (63–126 days), Mochlodon (77–140 days), Pinacosaurus (75 days), Edmontonia (279 days), and Changchunsaurus (58 days) [ 52 , 53 ]. In Triceratops and hadrosaurs, the mean tooth formation times range from 132 to 381 days [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the mesiodistal thin-section of rPM5 in the early juvenile CUGW VH132, the tooth formation time is 25 days in the premaxilla (Table 3). This duration is lower than Hungarosaurus (63–126 days), Mochlodon (77–140 days), Pinacosaurus (75 days), Edmontonia (279 days), and Changchunsaurus (58 days) [ 52 , 53 ]. In Triceratops and hadrosaurs, the mean tooth formation times range from 132 to 381 days [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The difference in tooth replacement rate is caused mainly by size differences in view of the similar DDAR. For comparison, the tooth replacement rate is faster than Mochlodon (140 days), Triceratops (83 days), hadrosaurs (range from 46 to 83 days), and ankylosaurs (53–120 days) [ 36 , 53 ]. The tooth replacement rate in Jeholosaurus is similar to those sauropods with dental batteries [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative and descriptive studies of rhabdodontid dietary ecology suggest these ornithischians were specialized, high-fiber herbivores that occupied dietary niches distinct from those of hadrosauromorphs and nodosaurids [ 111 ], with possible overlap among early ceratopsians [ 108 ]. However, to date, our understanding of ornithischian niche partitioning and sympatry in rhabdodontomorph-bearing assemblages is limited, stemming predominantly from the mosaic Late Cretaceous record of the European archipelago, with inconsistently resolved taxa from Australia and North America.…”
Section: Discussionmentioning
confidence: 99%
“…Many avian traits, such as feathers, genomic contraction and hollow bones, were also thought to be adaptations for flight, but research in the last four decades has revealed other functional contexts [6][7][8][9][10][11][12][13].Mesozoic dinosaurs were tremendously successful-they occupied a diverse range of ecological niches comparable to modern mammals [14,15]. Niche partitioning among sympatric dinosaurs can be inferred by differences in tooth shape, deposition of dentin, tooth replacement rates and jaw mechanics [16]. However, unlike mammals, several dinosaur groups evolved keratinous beaks;…”
mentioning
confidence: 99%
“…Mesozoic dinosaurs were tremendously successful-they occupied a diverse range of ecological niches comparable to modern mammals [14,15]. Niche partitioning among sympatric dinosaurs can be inferred by differences in tooth shape, deposition of dentin, tooth replacement rates and jaw mechanics [16]. However, unlike mammals, several dinosaur groups evolved keratinous beaks;…”
mentioning
confidence: 99%